Risk assessment in the digital economy - Khodyrieva, O. O.; Pererva, P. G. (My University, 2023)
It has been proven that the concept of the digital economy, its model component, is a kind of virtual environment, the content of which more organically and in detail complements the existing realities, integrates with them. Modern development trends have led to the widespread introduction of the digital economy and, in connection with this, to the rethinking of basic concepts, in particular the concept of risk. In the realm of the digital economy, it makes sense to argue that digital risk exists.
Оцінка ризиків у цифровій економіці
Keywords: information technologies; risk; digital economy; evaluation; enterprises